Mechanism and evaluation method of rock burst prevention in coal mines using surface hydraulic fracturing - Yuzhen MA; Yongtao GAO; Sitao ZHU; Junfeng PAN; Kaiwen XIA; Xiufeng ZHANG; Fuxing JIANG; Jinhai LIU; Bing WANG; Yang CHEN; Cai YAN (Meitan xuebao)
In response to the lack of understanding of the rock burst prevention mechanism and the absence of evaluation methods for the prevention effect in surface hydraulic fracturing, this study focused on the hydraulic fracturing construction at No 401102 working face of the Mengcun Coal Mine. The research employed theoretical analysis, on-site monitoring, numerical simulation, and other methods to investigate the overlying strata structure and the movement form and process control mechanism of thick and hard key strata in the mining area after surface hydraulic fracturing. The study analyzed the characteristics of the dynamic load disturbance induced by the movement form and process changes of the thick and hard key strata and the characteristics of the influence of changes in the overlying rock structure on the degree of static load accumulation after the implementation of ground hydraulic fracturing in the mining space. It revealed the mechanism of ground hydraulic fracturing for preventing and controlling rock-bursts. Furthermore, the study proposed and applied a method for evaluating the effectiveness of surface hydraulic fracturing construction to prevent rock-bursts in coal mines, and the conclusions were as follows: ground hydraulic fracturing broke a complete thick hard rock formation into several fractured strata along the main fracture. The movement forms and processes of thick and hard rock strata was regulated to rotary or slippery movement, resulting in a reduction in the energy of mining-induced earthquakes and the equivalent additional disturbing stress in the working face. Additionally, the regulation of the overburden structure of the working face led to a change in the degree of static load concentration in the working face, thereby lowering the level of overburden pressure. Consequently, this reduced the scope of rock-burst hazard zones; Compared with the static load of the working face, the effect of ground hydraulic fracturing measures in regulating the dynamic load was more significant. Through theoretical calculations, the additional equivalent working face disturbance stress caused by the movement of the overlying rock after fracturing in the 401102 working face was 1.72 MPa, the peak strike support pressure was 42.26 MPa, and the influence range of the impact hazardous area was 12 m. These values were 76.0%, 8.5%, and 47.8% lower, respectively, than those observed with non-fracturing measures; In the fracturing particle flow numerical model, the fracturing main fissure provided a path for the development of the overlying rock structure, accelerated the extension of fissure development in the vicinity of the fractured layer position, and induced fractured strata to undergo slewing or sliding movement. Consequently, the height of the final overburden fissure development of the working face increased by 30 m, and the peak of the strike-supporting pressure at each measurement point was reduced by an average of 5.16 MPa; The evaluation parameter W was calculated as 0.62 for the rock burst prevention effect of the 401102 working face, indicating an excellent comprehensive evaluation of the fracturing rock burst prevention effect.